China’s social assistance and poverty reduction policy (2022)
China’s Social Assistance and Poverty Reduction Policy is an essential requirement for alleviating poverty and guaranteeing the basic needs of people who live at the bottom of society and are unable to obtain a source of livelihood through their own means. This paper summarizes the development of China’s policy and its social assistance main measures aimed at fighting poverty and analyzes its possible contributions to alleviating global poverty. The main findings of the study are that: social assistance is a key factor within the poverty reduction policy and such policy is the foundation of the poverty reduction policy; an exemplary institutional synergy has resulted from the multi-tiered poverty reduction policy system; the comprehensive poverty reduction policy and the poverty alleviation and development policy have been connected effectively; the grass-roots services and supervision mechanisms have also been continuously improved. Additionally, sustained economic development has provided stable financial support for implementing its policy and its government has committed to improve the system, adding importance to building a security net for people’s livelihood, and establishing a comprehensive policy system for poverty reduction. Forming a responsibility mechanism led by the government and supplemented by social forces[1], China has constructed a policy adjustment mechanism compatible with social development, to innovate grassroots social governance, aimed at continuously improving the performance of poverty reduction. A look at China’s poverty reduction historical process can inspire the world’s poverty governance.